Pengaruh Factors Affecting Village Fund Management With Village Apparatus Competence as a Moderating Variable - Gusdalimah, Gusdalimah; Taufik, Taufeni; Savitri, Enni (Indonesian Journal of Economics, Social, and Humanities, 2024)
The central government provides a budget to the village in the form of village funds to increase the budget for development, services, and community empowerment that have been budgeted by the government, which is large enough each year to be given to the village. The purpose of this study was to examine the effect of the use of village financial systems, community participation, and accessibility of financial statements on the management of village funds with the competence of village officials as moderating variables in Rokan Hulu Regency. The population in this study were villages in Rokan Hulu Regency as recipients of village funds, namely 139 villages. The sampling technique used in this study was proportional stratified random sampling, and the respondents in this study consisted of: village head, village secretary, head of finance, and BPD, so that the respondents amounted to 412 people. The data collection technique used in this study was to use a questionnaire. The data analysis used Warp PLS. The results of this study indicate that the utilization of village financial systems, community participation, and accessibility of financial statements affect the management of village funds. The competence of village officials moderates the effect of the use of village financial systems and community participation on the management of village funds. However, the competence of village officials does not moderate the effect of the accessibility of financial statements on the management of village funds.